Динамический структурный фактор неидеальной пылевой плазмы с частицами конечных размеров - Еримбетова, Лаззат Тастанбековна; Давлетов, Аскар Ербуланович; Архипов, Юрий Вячеславович; Ткаченко Гурски, Игор Михайлович (Recent Contributions to Physics, 2019)
The aim of the study is to determine the effect the finite size of dust particles has on the static and dynamic characteristics of the dust component of a plasma. A model expression, obtained from the linear density-response theory with the plasma dielectric function in the random phase approximation, is used as an interaction potential between dust particles. The static structure factor of dust particles is evaluated from the reference hypernetted-chain approximation, which inherently contains the hard sphere model handled within the Perkus-Yevik closure. The appearance of maxima and minima is found in the curves of the static structural factor, indicating the formation of short- and long-range orders in the arrangement of dust particles. The dynamic structure factor is restored using only its static counterpart based on the self-consistent method of moments, which assumes that the second derivative of the dynamic structure factor with respect to frequency vanishes at the origin. Thus, an analytical expression has been put forward for the dynamic structural factor, which is valid in a wide range of parameters of plasma nonideality and dust packing fractions. At low packing fractions, the dynamic structure factor coincides with the results of molecular dynamics simulations, but with increase of the packing fraction, the maximum of the dynamic structure factor grows and shifts to the left or right in frequency, depending on the wavenumber.